Manganese toxicity in Portuguese Cambisols derived from granite: causes, limitations of soil analyses and possible solutions - Carvalho, Mário (2015)
Cambisols are the major soil type in Portugal. The yield of annual crops in these soils is generally poor, and the situation is aggravated in wet winters. In the south of Portugal, manganese toxicity has been identified as the major cause of poor growth and leaching as the main reason for the negative effect of rainfall observed in Cambisols derived from granite Manganese toxicity also appears to be present in the Cambisols in other regions of Portugal. Manganese toxicity is cross-related to the magnesium concentration, either in the soil solution or in plant shoots. Therefore soil amendment using dolomitic limestone is needed to overcome the problem. Current soil test methods are unable to predict the level of Mn toxicity. However, new approach using the extraction of soil solution is proposed, although further work is needed to fully implement the method.